Reflex\~oes sobre a PEC No 287/2016 e suas alteraç\~oes: Limites e possibilidaded para a carência mínima para aposentadoria voluntária no Regime Geral de Previdência Social - Graziela Ansiliero (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The Social Security Reform Bill (PEC) no 287/2016, along with its subsequent modifications, attempts to promote important and necessary parametric adjustments in the Brazilian Social Security system, with clear focus on its social insurance pillar. Put it simply, regarding the General Social Insurance System (RGPS), the original proposal stablished the stiffening of the eligibility requirements for claming benefits, mainly (but not only) old-age pensions, for which the insured would be required to meet newly established or increased minimum access criteria (mostly in terms of age and waiting periods), common to all types of insured workers (65 years of age and 25 years of contributions). The sole modality for voluntary retirement remaining in the post-reform RGPS (when the unavoidable transitional rules are no longer applicable), would demand, for the urban clientele, a minimum age of 65 (men) or 62 years (women) and a minimum waiting period of 25 years of effective financial contributions; as for the rural clientele, the minimum age would be of 60 (men) or 57 years (women), with the minimum waiting period maintained at the current level of 15 years (although, unlike the ongoing prevailing rules, there would be a requirement for actual financial contributions, not only for proof of rural activity). The current version of the reform bill preserved the minimum waiting period of 15 years in force at RGPS (for both clienteles, urban and rural, with the latter maintaining the sufficiency of the proof of rural activity as condition for retirement) and the rural minimum retirement age for women (55 years), in addition to maintaining the substitutive proposal for the urban minimum retirement ages (65 (H), 62 (M)). The analyzed data, extracted from the National Household Sample Survey (PNAD) and administrative records of the RGPS, indicate substantive improvements on social security coverage in the last decades (considering employed workers and the elderly) and in the contribution density measured for retirees (estimated in terms of the evolution on the average number of years of contribution or activity registered up until the time of retirement). Still, there seem to be evidence of possible limits for the continuous enhancement of these indicators, at least to the extent necessary to face this aspect of the reform proposal, perhaps too strict when taken into consideration the Brazilian socioeconomic reality and perspectives and in the light of what is internationally considered to be the more appropriate approach in this matter. The PEC no 287/2016 has important merits and conceives a more sustainable social insurance system, but some of its aspects, such as the recently proposed adjustments to the minimum waiting period for retirement, were properly reformulated.
Keywords: I38; H55; 330; social insurance; social insurance reform; minimum waiting period to entitlement of benefits; social insurance coverage